For the three vectors
a = ( 2 , − 1 , 0 ) , b = ( − 4 , 2 , 5 ) , c = ( 0 , 0 , 3 ) ,
what is 6 a − 4 b + 2 c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
the answer is 28, -14, -14 !!!!!!! Hey I am hritik kaushik from radhika appts! flat no.73
6 * (2, -1, 0) - 4 * ( -4, 2, 5) + 2 * (0, 0, 3) = (12, -6, 0) + (16, -8, -20) + (0, 0, 6) = (28, -14, -14)
During addition of vectors the components get added. So add them accordingly after multiplying
We have to take one value for each variable at a time.
a = ( 2 , − 1 , 0 ) , b = ( − 4 , 2 , 5 ) , c = ( 0 , 0 , 3 )
So, the first value of 6 a − 4 b + 2 c is:
6 a − 4 b + 2 c = 6 × 2 − 4 × ( − 4 ) + 2 × 0
6 a − 4 b + 2 c = 1 2 + 1 6 + 0
6 a − 4 b + 2 c = 2 8
Second value of 6 a − 4 b + 2 c is:
6 a − 4 b + 2 c = 6 × ( − 1 ) − 4 × 2 + 2 × 0
6 a − 4 b + 2 c = − 6 − 8 + 0
6 a − 4 b + 2 c = − 1 4
Third value of 6 a − 4 b + 2 c is:
6 a − 4 b + 2 c = 6 × 0 − 4 × 5 + 2 × 3
6 a − 4 b + 2 c = 0 − 2 0 + 6
6 a − 4 b + 2 c = − 1 4
Thus, the answer is: 6 a − 4 b + 2 c = ( 2 8 , − 1 4 , − 1 4 )
Me hate math
Problem Loading...
Note Loading...
Set Loading...
6 * (2, -1, 0) - 4 * ( -4, 2, 5) + 2 * (0, 0, 3) = (12, -6, 0) + (16, -8, -20) + (0, 0, 6) = (28, -14, -14)